EFEKTIVITAS EDUKASI UNTUK MENINGKATKAN PENGETAHUAN MASYARAKAT DALAM PENANGANAN RINITIS ALERGI - Amelia Lorensia; Nina Purnama Sari (Jurnal Ilmiah Manuntung, 2017)
Allergic rhinitis is a common disorder of the breathing that can affect one's productivity and shock. Therefore it is necessary knowledge in self-management to eliminate exposure to allergens that can increase the symptoms of allergic rhinitis. The purpose of this study is to determine the effectiveness of education in improving public knowledge about drugs allergic rhinitis. The research method is experimental pre-sampling with adult sampling through purposive sampling. Measurement of experience conducted for 3 times, ie before getting education (pre test), post-education (post test), and one month after received education (follow up test). The research conducted in May-July 2016, involving 30 people. The results showed that there were significant differences between pre test and post test (0,000 <p (0.05)) and between pre test and follow-up test (0.000 <p (0,05)). However, no changes occurred between post test and follow up test. So education is effective in improving public knowledge in the treatment of allergic rhinitis.